Monitoring of Deformation Behaviour of Unsaturated Soil Slope using Distributed Optical Fibre Sensor - Awang Ismail, Dayangku Salma; Kassim, Azman (International Journal of Integrated Engineering, 2020)
A distributed optical fibre sensing system named Brillouin Optical Time Domain Analysis (BOTDA) is used to monitor the strain development of a laboratory soil slope model. The technology is yet to be fully implemented due to uncertainties of attachment method or the best way to set up optical fibre sensors for geo-structure health monitoring.  The aim of study is to evaluate the deformation behaviour subjected to the development of horizontal strains from Brillouin-based optical fibre sensor of a residual soil slope under loading impact using BOTDA technology.  In this study, a soil-embedded strain sensor placement approach was proposed to be installed in the 1g model of soil slope which was achieved via the horizontal planting of a three-layered optical fibre cable in S-curve forming slope. In this paper, however, only pilot tests result is demonstrated for preliminary data interpretation purposes.  From the preliminary laboratory tests, the results show the soil-embedded sensing fibre arrangement has efficiently detected and measured the horizontal strain deformation due to loading. Therefore, it can be concluded that the sensing fibre was well-responded with the soil movement under loading impact.